Recursos educativos abiertos para el desarrollo del pensamiento lógico matemático en la asignatura de Matemática en estudiantes de Primero de Bachillerato General Unificado - Contento Japón, Miryan Beatriz (2024)
Open Educational Resources (OER) are free Access materials that facilitate teaching and learning, and promote the development of mathematical logical thinking for the resolution of exercises and problems. This research is focused on analyzing open educational resources for the development of mathematical logical thinking in the subject of Mathematics in First Year Unified General Baccalaureate students. To achieve this, the study was based on a qualitative approach, with a descriptive scope, of a documentary type using documentary review techniques and indexing, accompanied by instruments such as: research logs, bibliographic and content files. The most relevant characteristics of OER are: inclusion and detailed explanation of problem situations, self-learning, freedom to modify mathematical contents, and elements such as: educational training contents, tools and implementation. These resources provide easy access to sufficient information for students to improve their knowledge by being active and innovative. Keywords: open educational resources, logical thinking, mathematics, teaching, learning.